General practitioners' views on reattribution for patients with medically unexplained symptoms: a questionnaire and qualitative study - Dowrick, Christopher; Gask, Linda; Hughes, John G.; Charles-Jones, Huw; Hogg, Judith A.; Peters, Sarah; Salmon, Peter; Rogers, Anne R.; Morriss, Richard K. (BioMed Central, 2008)
Background: